Testing the primary and convergent retrieval model of recall: Recall practice produces faster recall success but also faster recall failure. - Hopper, William J.; Huber, David E. (Memory & Cognition, 2019)
The primary and convergent retrieval (PCR) model assumes that the act of successful recall not only boosts associations between the item and retrieval cues but additionally strengthens associations within the item (i.e., between the features of an item), speeding the rate of information retrieval from memory. The latter effect is termed intra-item learning and is a unique benefit of recall practice (i.e., the "testing effect"). Prior work confirmed the prediction that recall practice produces faster subsequent recall than restudy practice even if accuracy is higher following restudy. The current study replicated this result, but also examined the downside of recall practice: that after a failure to recall during practice, participants will be faster in their failure to recall on a subsequent recall test. This prediction was confirmed in a multisession cued recall experiment that collected accuracy and recall latency measurements for no practice, recall practice, or restudy, with an immediate or delayed final test. The linear ballistic accumulator model was fit to latency distributions, and model comparison determined that these effects reflect differences in drift rates, as predicted by the PCR model.